Influence of hydrological factors on formation of radionuclide contamination of the hydrobionts - O. M. Volkova; V. V. Belyaev (Ядерна фізика та енергетика)
Influence of water exchange reservoir speed and peculiarities of radionuclides transportation with water masses of Dnieper reservoir to the process of accumulation 137Cs of hydrobionts of different trofic links was investigated. The dependence of levels of accumulation 137Cs of the Fishes from the speed of water-reservoir exchange is defined. The influence of peculiarities of transportation along the cascade of the Dnieper transportation water reservoir, which were polluted during the spring floods, on the formation of137Cs content in higher aquatic plants are determined. Formation of levels of137Cs accumulation by the fishes depends on nuclear fall-out density to surface of the reservoir and on the quantity of radionuclide in the ecological system.